THE ROLE AND SOCIAL SIGNIFICANCE OF INTERCULTURAL COMMUNICATION COMPETENCE IN THE PROCESS OF GLOBALIZATION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the role and social significance of intercultural communication competence (ICC) in the context of contemporary globalization. The study analyzes the theoretical foundations of intercultural competence, its structural components, and its practical importance for individuals navigating multicultural environments. Drawing on established frameworks in intercultural communication theory, the paper argues that ICC is not merely a professional skill but a critical social capacity that enables productive interaction across cultural boundaries. The article further explores how globalization intensifies both the need for and the complexity of intercultural communication, highlighting the challenges posed by cultural stereotyping, ethnocentrism, and communicative misunderstandings. Special attention is given to the role of educational institutions, particularly higher education, in fostering ICC among students and future professionals. The findings suggest that systematic development of intercultural competence contributes to social cohesion, conflict prevention, and sustainable cross-cultural cooperation at both individual and societal levels.